If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x-6 = 0
x-6 = 0
x-6 = 0
x-6 = 0 // + 6
x = 6
x in (-oo:6) U (6:+oo)
-1 = (2*x-3)/(x-6) // - (2*x-3)/(x-6)
-((2*x-3)/(x-6))-1 = 0
(-1*(2*x-3))/(x-6)-1 = 0
(-1*(2*x-3))/(x-6)+(-1*(x-6))/(x-6) = 0
-1*(2*x-3)-1*(x-6) = 0
9-3*x = 0
(9-3*x)/(x-6) = 0
(9-3*x)/(x-6) = 0 // * x-6
9-3*x = 0
9-3*x = 0 // - 9
-3*x = -9 // : -3
x = -9/(-3)
x = 3
x = 3
| -4-4x=29-5 | | y=(f-d)x+3 | | 3/5x-1/10x=12 | | 35×1/2 | | 1/3(17)(15)(20)=x | | 2-7ab+3a^2b=0 | | w/6=-24 | | 1/3(17)(15)(20)= | | 10x+2x=14+x | | (5x-7)(3x+4)= | | 3x*(x+5)= | | 5x^2-90x+400=0 | | (13b-4)-3(4b+3)=-7 | | 3y=-5x-15 | | -3=-14u | | 3x^2-4x-72=0 | | 5p+5.95=88.20 | | 0.4x-1.2=2.6forx | | 25x+8-28x=4-5 | | 52=-m/6 | | 256+vt-s=0forv | | 7k^2+18=14k | | 5x-1/2x=5 | | x+.6x=14 | | 0.885t^2-0.934t+1.718=0 | | 6(x-4)/3 | | 4/15=y/10 | | 7(2p-1)=10-3p | | (x-5)^2/3=16 | | 125=-5x | | 5y=32x+5 | | Fx=12+10x-5x |